Polymeric materials in sustainable development – from the need to use to the need for wear Part II. Return to monomers - Kijeński, Jacek (Polimery, 2021)
The critical analysis of the strategies of the prevention of the rise and accumulation of polymeric wastes was performed and the proposals for their processing according to the Packet for the Circular Economy have been presented. The weak points of these strategies resulting from contradictions with economic criteria, thermodynamics rules, real aims of the environment protection and the community expectations, finally also from the knitted influence of the EU administration onto structure of household and industrial articles dominating on the European market were demonstrated. The estimation of the real chances of the polymeric wastes recycling according to the principal goal of the CE, which is the come-back to the row material streams allowing the reduction of the crude oil and other mineral sources consumption have been also carried out. It was shown that the most realistic resolutions of the problem are: the return to the monomers on the way of gasification (or co-gasification) of plastic wastes (polyolefins) and processing of methanol synthesized from syngas by MTO or MTP methods and by the thermal or chemical depolymerization carried out in the case of susceptible to these processes (e.g. PET or PUR).